Republic of Uzbekistan : 2006 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Uzbekistan. (IMF Staff Country Reports; Country Report ;, 2007)
The 2006 Article IV Consultation on the Republic of Uzbekistan highlights the economic outlook and policy challenges. The banking system's ability to fulfill its intermediary role has been constrained by limited credit expansion, given the strong growth in net foreign assets and the need to control the growth of reserve money. Executive Directors commended the Uzbek authorities on the strong performance of the economy, which has been supported by a favorable external environment, improvements in macroeconomic policies, and gradual progress in structural reforms.